Characterization of Bartonella species infecting North American Triatominae (kissing bugs) - Kogler, Alexandra (Jihočeská univerzita, 2021)
The aim of this thesis was to characterize Bartonella spp. within T. rubida gut microbiomes, using multilocus sequence typing (MLST), and to determine its incidence at different sampling localities.
Characterization of Bartonella species infecting North American Triatominae (kissing bugs)
Keywords: kissing bugs; T. rubida; Bartonella; kissing bugs; T. rubida; Bartonella